OBSERVATIONS ON THE HYDROLOGY OF THE HOOGHLY ESTUARY - Bose, Benoy B (Indian Journal of Fisheries, 2015)
Observations on the hydrology of the Hooghly estuary were taken up with a view to collecting basic information necessary for understanding the behaviour of fish and the pattern of fisheries in the estuary. A preUminary picture of the data collected till August 1951 was cited in a recent communication (Dutta et ah, 1954) and the present paper embodies the results of investigations carried out until April 1955.